Peran Tata Usaha dalam Pengelolaan Arsip Berbasis Digital di Madrasah Tsanawiyah Negeri 3 Jember - Sabrina Salsabila; Nur Ittihadatul Ummah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study was motivated by the need for madrasahs to adapt to technological developments, particularly in document management, which was previously done manually. The purpose of this study was to describe the role of administration in digital archive management at MTsN 3 Jember, identify the obstacles that arose, and explain the efforts made to overcome these obstacles. The research used a descriptive qualitative approach with data collection through interviews, observation, and documentation. The results showed that administration played an important role as the main manager of digital documents through the use of applications such as SIMPEG, TTE, and SAKTI, as well as the use of cloud-based storage to maintain the security and ease of access to archives. The obstacles faced include the limited digital capabilities of employees, technical disruptions to applications, and suboptimal technological infrastructure. However, various efforts have been made, including performing regular backups, improving the organization of digital documents, and enhancing staff capabilities through independent learning. This study confirms that the success of digital archive management requires synergy between human resource readiness, technological support, and managerial policies that support the transformation of madrasah administration.